Group Guidance Services Through The Game "Let's Clapping Concentration" To Improve Memory At State Elementary School 3 Langkai Palangka Raya - Sangalang, Oktamia Karuniaty; Suriatie, Mimi; Pangestie, Esty Pan; Sukarningsi, Susi (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Teachers play a role in Guidance and Counseling services at school. The purpose of this study was to determine teacher participation in implementing group guidance services using the "Ayo, Tepuk Fokus" game method at State Elementary School 3 Langkai Palangka Raya.The sample consisted of 28 teachers at the school. The primary data collection tool used was the Checklist technique, which involved creating a list of questions addressed to all teachers at State Elementary School 3 Langkai Palangka Raya To analyze the data and test the hypothesis that teachers participate in implementing group guidance services at the school, the researcher used percentage calculations. The study's results showed that all components of the research objectives were implemented with a reasonably high percentage by teachers at the school. The results of this study are based on the Checklist (yes/no) and not on the variation. This means that teachers participate and support Group Guidance Services at State Elementary School 3 Langkai Palangka Raya.